Pengaruh Variasi Lubang terhadap Koefisien Debit pada Wadah Terbuka Berisi Oli - Lia Yunita (Jurnal Mekanika dan Sistem Termal, 2016)
This study aims to determine the effect of variation of the coefficient of discharge hole in an open container. The flow of fluid out of the hole has a cross-sectional area which is different from the actual cross-sectional area, the phenomenon is called venous kontrakta. Comparison of real debit and debit theoretically called the discharge coefficient (Cd). Experimental method used to determine the coefficient of discharge of oil flow in open containers using the software help logger pro 3.8.4. In this study, it was carried out various forms holes that of a circle and a triangular hole using an open container (jar) containing oil. The experimental results show that the circle-shaped hole has a coefficient of discharge is greater than the triangular hole.